2017
DOI: 10.1016/j.nano.2016.12.019
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms that determine nanocarrier targeting to healthy versus inflamed lung regions

Abstract: Inflamed organs display marked spatial heterogeneity of inflammation, with patches of inflamed tissue adjacent to healthy tissue. To investigate how nanocarriers (NCs) distribute between such patches, we created a mouse model that recapitulates the spatial heterogeneity of the inflammatory lung disease ARDS. NCs targeting the epitope PECAM strongly accumulated in the lungs, but were shunted away from inflamed lung regions due to hypoxic vasoconstriction (HVC). In contrast, ICAM-targeted NCs, which had lower wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 33 publications
(28 reference statements)
4
52
2
Order By: Relevance
“…A recent study in a spatially heterogeneous mouse model of acute respiratory distress syndrome found a similar enhancement of nontargeted carriers in regions of organ damage (39). Thus, our findings would seem to corroborate in human organs this previous observation in animal models.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study in a spatially heterogeneous mouse model of acute respiratory distress syndrome found a similar enhancement of nontargeted carriers in regions of organ damage (39). Thus, our findings would seem to corroborate in human organs this previous observation in animal models.…”
Section: Discussionmentioning
confidence: 87%
“…Developing and testing new therapeutics for lung diseases starts with using outstanding preclinical models that recapitulate key aspects of human lung disease [15,18]. Intratracheal administration of injurious agents or inducing non-specific systemic inflammation either create bland injury that falls short of the severe injury that often produces the greatest mortality or it creates such a severe injury that studying long-term regeneration is not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Radiolabeling nanoparticles Rat IgG (ThermoFisher catalog #31933) was labeled with I-125 via Pierce Iodination Beads (ThermoFisher catalog # 28665). We then conjugated the IgG to nanoparticles using our published protocol [15]. In brief, 100 L of polystyrene NPs were buffer exchanged Zeba™ Spin Desalting Columns, 7K MWCO, 0.5 mL (ThermoFisher catalog # 89882), exchanging for 50 mM MES buffer at pH 5.2, finally putting the buffer-exchanged beads into 1.5 mL Eppendorf tubes.…”
Section: Nanoparticle-based Tracking Of the Location Of Instillate Inmentioning
confidence: 99%
See 1 more Smart Citation
“…I have recently shown that PECAM-targeted PELs accumulate in the lungs of mice at greater than 300-fold higher levels than typical small-molecule drugs (Figure 2A) (7). Further, those PELs appear to concentrate in the alveoli ( Figure 2B).…”
Section: Opinions and Ideasmentioning
confidence: 95%